PERAN MAHASISWA KKNT MBKM DALAM MENUMBUHKAN KESADARAN ANAK TERHADAP LINGKUNGAN MELALUI PENGELOLAAN SAMPAH DI SD SETREN, KECAMATAN REJOSO, NGANJUK - Rachmawati, Andini; Prathama, Ananta (UNIVERSITAS SERAMBI MEKKAH, 2024)
Waste is leftover material resulting from human activities or natural processes that is considered useless or has no economic value, so waste can become an environmental problem that requires serious attention if not managed properly. Along with population growth, the volume of waste in the environment also increases. The lack of public awareness about waste management is also a problem that exists in the Setren Elementary School environment as evidenced by the fact that there are still many students who litter and do not know what waste management steps are. This activity uses a socialization method about providing understanding to raise awareness of elementary school students to be environmentally conscious. With this socialization activity, there is a positive change from students with growing awareness of the environment, especially waste management issues. The sustainability of this program is expected to create a clean and healthy village environment, free from waste, and increase awareness of the environment in students.